The Fast-Growing Brucella suis Biovar 5 Depends on Phosphoenolpyruvate Carboxykinase and Pyruvate Phosphate Dikinase but Not on Fbp and GlpX Fructose-1,6-Bisphosphatases or Isocitrate Lyase for Full Virulence in Laboratory Models - Zúñiga-Ripa, Amaia; Barbier, Thibault; Lázaro-Antón, Leticia; de Miguel, María J.; Conde-Álvarez, Raquel; Muñoz, Pilar M.; Letesson, Jean J.; Iriarte, Maite; Moriyón, Ignacio (Frontiers in Microbiology, 2018)
Bacteria of the genus Brucella infect a range of vertebrates causing a worldwide extended zoonosis. The best-characterized brucellae infect domestic livestock, behaving as stealthy facultative intracellular parasites. This stealthiness depends on envelope molecules with reduced pathogen-associated molecular patterns, as revealed by the low lethality and ability to persist in mice of these bacteria. Infected cells are often engorged with brucellae without signs of distress, suggesting that stealthiness could also reflect an adaptation of the parasite metabolism to use local nutrients without harming the cell. To investigate this, we compared key metabolic abilities of B. abortus 2308 Wisconsin (2308W), a cattle biovar 1 virulent strain, and B. suis 513, the reference strain of the ancestral biovar 5 found in wild rodents. B. suis 513 used a larger number of C substrates and showed faster growth rates in vitro, two features similar to those of B. microti, a species phylogenomically close to B. suis biovar 5 that infects voles. However, whereas B. microti shows enhanced lethality and reduced persistence in mice, B. suis 513 was similar to B. abortus 2308W in this regard. Mutant analyses showed that B. suis 513 and B. abortus 2308W were similar in that both depend on phosphoenolpyruvate synthesis for virulence but not on the classical gluconeogenic fructose-1,6-bisphosphatases Fbp-GlpX or on isocitrate lyase (AceA). However, B. suis 513 used pyruvate phosphate dikinase (PpdK) and phosphoenolpyruvate carboxykinase (PckA) for phosphoenolpyruvate synthesis in vitro while B. abortus 2308W used only PpdK. Moreover, whereas PpdK dysfunction causes attenuation of B. abortus 2308W in mice, in B. suis 513 attenuation occurred only in the double PckA-PpdK mutant. Also contrary to what occurs in B. abortus 2308, a B. suis 513 malic enzyme (Mae) mutant was not attenuated, and this independence of Mae and the role of PpdK was confirmed by the lack of attenuation of a double Mae-PckA mutant. Altogether, these results decouple fast growth rates from enhanced mouse lethality in the brucellae, suggest that an Fbp-GlpX-independent gluconeogenic mechanism is ancestral in this group and show differences in central C metabolic steps that may reflect a progressive adaptation to intracellular growth.